QUALITATIVE MODELING OF ECOLOGICAL TOURISM DEVELOPMENT IN ThE ALTAI REPUBLIC - D. S. Khazova (Финансы: теория и практика)
The eco-tourism development in the Altai Republic is an up-to-date task since the formation of the tourist sector will boost the whole regional economy of the Altai Republic, provide significant social and economic benefits not only at the regional but also at the nation-wide level, allow partial solution of the problem of uneven distribution of economic resources and the manpower in Russia without upsetting the balance between the environment and the economic reproduction. This research work includes methods of qualitative modeling as well as elements of the graph theory and the cluster analysis. All analytical methods were realized by using the R programming language. In this research the basic principles of the qualitative modeling that allows taking into account qualitative factors influencing the tourist industry are analyzed, a qualitative model of the ecological tourism development is developed, the optimum directions of investments in the tourist industry of the Altai Republic are defined. The basic provisions of the article and the research findings can be used for creation of an effective tourism management system both at the level of regional authorities and the level of tourist industry subjects. The qualitative modeling algorithm has an independent scientific and practical value and can be used for high-quality modeling of various systems of regional economy, including modeling of the tourist sector.